Identificação por Maldi-Tof MS de isolados de Aspergillus seção Nigri e avaliação do potencial biotecnológico na produção de biossurfactantes - Faria, Lucas Vieira de (2015)
Species belonging to section Nigri form a subgroup of genus Aspergillus, and are cosmopolitan. Many species of this section are used in food and fermentation industries, being A. niger the most reported, presenting GRAS status. However, this section is considered by many taxonomists as one of the most difficult to identify due to high genetic variability. Surfactants are amphipathic molecules that present two portions in the same molecule: a hydrophilic portion and a hydrophobic portion. Biosurfactants are a group of many molecules produced by different microorganisms and mainly classified by chemical structure and microbial origin. The objectives of this work were to identify 32 Aspergilus section Nigri fungal isolates by means of the MALDITOF MS technique, and test the biosurfactant production capacity of three Aspergillus niger isolates, using bacteria Bacillus subtilis CCMA 0087 as control. We tested three different protein extraction methodologies by MALDITOF MS, comparing them by means of grouping in dendrograms. The results showed that the grouping could vary depending on the methodology used. Regarding biosurfactant production capacity, the fungi isolates were tested to obtain the emulsification index, considering many aspects for its favoring, rheological analyses and a phytotoxicity study of lettuce seed extracts (Lactuca sativa L.). The results suggest that isolate B. subtilis CCMA 0087 produced the most emulsifiers, and pH 5.0 and 7.0, as well as day 1 presented the best data. The extracts did not differ for rheological parameters, and all were phytotoxic.